A Technoeconomic Resilience and Exergy Analysis Approach for the Evaluation of a Vaccine Production Plant in North-East Colombia (2022)
Influenza is an acute infection that can cause diabetes and heart and lung disease disorders. This illness affects more than 9 million people around the world. The best way to control the transmission of the virus is vaccination. Studies, performed in Santander, Colombia, have found the existence of this disease. Despite the above, there are no companies dedicated to producing influenza vaccines in Colombia. For the first time, exergetic analysis and technical-economic resilience are being performed as combined decision-making tools for the evaluation of an influenza vaccine production plant. The results of exergetic analysis showed that the global exergy efficiency of the process was estimated at 93%. The exergy of waste that resulted was 61.70 MJ/h. The most critical stage of the process is milling, representing 83% of the total destroyed exergy. On the other hand, the results of technoeconomic resilience showed that the break-even point capacity of the process is 2503.15 t/y, representing only 24% of the installed capacity of the plant. The analysis of the effect of raw materials cost on profits showed that the process only resists a rise of 4% in the cost of raw materials, and higher values show economic losses. A value of 215,500 USD/t establishes a critical point for the normalized variable operating costs because higher values do not provide a return on investment.